Answer:
cos(a + b) =
Step-by-step explanation:
cos(a + b) = cos(a).cos(b) - sin(a).sin(b) [Identity]
cos(a) =
cos(b) =
Since, terminal side of angle 'a' lies in quadrant 3, sine of angle 'a' will be negative.
sin(a) = [Since, sin(a) = ]
=
=
Similarly, terminal side of angle 'b' lies in quadrant 2, sine of angle 'b' will be negative.
sin(b) =
=
=
By substituting these values in the identity,
cos(a + b) =
=
=
=
Therefore, cos(a + b) =
4d + 12 = 4(d + 3)
Basically, you just need to determine what 4d and 12 have in common. In this case, they both divide evenly by 4. Therefore 4 (d + 3) = 4d + 12 according to the distributive property.
Answer:
Step-by-step explanation:
<h2>
</h2><h2>
</h2><h2>
</h2><h2>
</h2><h2>
</h2><h2>
</h2>
- hope it helps! -
<h2 />
Answer:
the number of pencils she bought
Step-by-step explanation:
p is just another variable like x or y
Answer:
2a2 + 4a + 7
Step-by-step explanation:
As, - (2a3 - 3a2 + 4a + 6) + (2a3 + 5a2 + 7)
= 2a2 + 4a + 13